2002
DOI: 10.1159/000067600
|View full text |Cite
|
Sign up to set email alerts
|

Is There Additional Information from Laparoscopic Ultrasound in Tumor Staging?

Abstract: Accurate preoperative staging of gastrointestinal malignancies is of major importance in the decision for adequate stage-related therapy. There is evidence that laparoscopy in combination with laparoscopic ultrasound is more accurate in the detection of intra-abdominal metastases than conventional preoperative imaging. Staging laparoscopy in combination with laparoscopic ultrasound is a minimally invasive technique that reveals intra-abdominal disseminated tumor spread and local tumor extent. Therefore laparos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…In the late 1980s and early 1990s, several studies proved IOUS to be more accurate in detecting liver metastases than the existing scanning methods, including extracorporeal US, CT, MRI, and surgical exploration [14,15,16,17]. In our study, ILUS was used to look for satellite lesions in all malignant cases; however, there were no positive findings.…”
Section: Discussionmentioning
confidence: 58%
“…In the late 1980s and early 1990s, several studies proved IOUS to be more accurate in detecting liver metastases than the existing scanning methods, including extracorporeal US, CT, MRI, and surgical exploration [14,15,16,17]. In our study, ILUS was used to look for satellite lesions in all malignant cases; however, there were no positive findings.…”
Section: Discussionmentioning
confidence: 58%
“…Six of the eight patients with false-positive results had intrahepatic cholestasis (compared to 3 of 15 patients with true-positive lesions), 1 had an infrahepatic abscess and the remaining patient had a right basal lung metastasis [39]. In the present study FDG PET identified disseminated disease in only 5 of 10 patients with positive laparoscopic findings and therefore cannot be seen as a substitute for laparoscopic staging [51,52,53]. …”
Section: Discussionmentioning
confidence: 62%
“…Several authors have demonstrated that laparoscopy is both safe and feasible to better assess resectability in pancreatic cancer patients before resorting to an open resective procedure, especially when associated with laparoscopic ultrasound [12,13,14,15,16,17,18]. Moreover, other authors have reported that such an approach can be adopted on a routine basis [19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The role of laparoscopy and laparoscopic US in staging pancreatic cancer is well established [12,13,14,15,16,17,18], and the procedure is considered routine before exploratory laparotomy for pancreatic resection by several high-volume centers [19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%